Pengenalan Penggunaan Alat Sondir Tanah 2,5 Ton Di Kawasan Kebun Raya Universitas Pahlawan - Hasibuan, Syahrial; Azriadi, Emon; Febryanto, Febryanto (Faculty of Engineering University of Pahlawan Tuanku Tambusai, 2025)
Geotechnical and soil mechanics investigations are one of the supporting elements in the construction of a building, starting from planning activities to implementation activities. Based on detailed and thorough geotechnical investigations during field implementation, it is expected to obtain accurate and reliable data so that a clear picture of the condition, nature and composition of soil/rock layers will be obtained. The purpose of this Community Development Activity is to provide education to civil engineering students on how to use a soil mechanics test tool using Sondir 2.5 ton capacity. In its implementation, the method used in this soil mechanics test is the cone penetration test method, which is a static soil test in the field using a metal cone with a sensor at the end, which is mechanically pressed into the ground at a constant speed. The results of the tests carried out at 2 (two) locations showed that there was a hard soil layer at the first location at a depth of > 10 meters, and no hard soil layer was found at the second location.